Pengaruh Mutu Layanan Pendidikan terhadap Kepuasan Siswa di MIS Mathlail Khoir Kecamatan Bojong Gede Bogor - Aulia Fauziah; Ahmad Riyadi; Nurul Hamidah (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Service quality based on education to evaluate student satisfaction at MIS Mathlail Khoir. The purpose of this study was to examine the effect of the quality of educational services on student satisfaction as well as to explain the quality of educational services and student satisfaction. The method used is a quantitative method with descriptive analysis with a population of 405 students and the sampling technique is cluster sampling of 100 students assigned to students in class V and class VI. These instruments are observation, documentation, and questionnaires. The data analysis method was carried out using correlation techniques and simple linear regression with the help of SPSS 26 software. The results showed that the quality of education services and student satisfaction in the school was said to be high with a mean value of X 75.83 while Y was 48.34. And shows that there is a significant influence between the quality of education services on student satisfaction from the regression equation obtained by Y'= 33.889+0.191X showing that there is a positive or unidirectional relationship, based on the calculation of the coefficient of determination of 10.5% while 89.5% is influenced by other variables not examined.